2007
DOI: 10.1094/pdis-91-3-0232
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbit aphid-borne yellows virus Is Prevalent in Field-Grown Cucurbit Crops of Southeastern Spain

Abstract: Despite the importance of field-grown cucurbits in Spain, only limited information is available about the impact of disease on their production. During the 2003 and 2004 growing seasons, systematic surveys were carried out in open field melon (Cucumis melo) and squash (Cucurbita pepo) crops of Murcia Province (Spain). The fields were chosen with no previous information regarding their sanitation status, and samples were taken from plants showing viruslike symptoms. Samples were analyzed using molecular hybridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
55
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 24 publications
12
55
0
6
Order By: Relevance
“…In general, symptoms consisted of interveinal chlorosis of the basal and older leaves with brittle and thick aspect. Similar symptoms have been described previously in cucurbit crops and found to be caused by CABYV (Kassem et al 2007;Lecoq et al 1992;Mnari-Hattab et al 2009). In addition, we noticed in symptomatic plants a reduction of the fruit number, but no effect on fruit quality and shape was detected (not illustrated).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In general, symptoms consisted of interveinal chlorosis of the basal and older leaves with brittle and thick aspect. Similar symptoms have been described previously in cucurbit crops and found to be caused by CABYV (Kassem et al 2007;Lecoq et al 1992;Mnari-Hattab et al 2009). In addition, we noticed in symptomatic plants a reduction of the fruit number, but no effect on fruit quality and shape was detected (not illustrated).…”
Section: Resultssupporting
confidence: 85%
“…This important percentage reflected the high incidence of CABYV in the fields (Table 1), and demonstrated the prevalence of CABYV in squash-growing fields of Egypt. Such a high incidence of CABYV was reported also in other countries like Lebanon, Spain, Tunisia and China (Abou-Jawdah et al 2000;Kassem et al 2007;Mnari-Hattab et al 2009;Shang et al 2009). In accord with our observations, all these regions had an abundance of aphids in open fields.…”
Section: Resultssupporting
confidence: 65%
“…Virus detection was performed as described by Kassem et al (2007). Samples were used immediately after collection for the detection of viruses by dot-blot hybridisation.…”
Section: Virus Detectionmentioning
confidence: 99%
“…Several counties of the Valencian Community (eastern Spain) have a longstanding tradition of cucurbits cultivation, in particular watermelon, melon, pumpkin, cucumber and squash. For instance, CABYV was found to be the prevalent virus infecting cucurbit crops of the Murcia region (South-eastern Spain), with incidences reaching 100% of the plants in affected fields (Kassem et al, 2007), and WMV was found to have a very high relative incidence in this and other Spanish areas (Luis-Arteaga et al, 1998;Moreno et al, 2004). Indeed, more than 35 different viruses have been described infecting cucurbits (Provvidenti, 1996), and at least ten of them have been identified in Spanish cucurbit crops causing infections with serious economic repercussions (Luis-Arteaga et al, 1998;Kassem et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Virus resistance is a major melon breeding objective, as several diseases caused by viruses have great economical impact in melon crops worldwide. Significant examples include the cucumovirus (family Bromoviridae ) Cucumber mosaic virus (CMV), the potyviruses (family Potyviridae ) Watermelon mosaic virus (WMV), Zucchini yellow mosaic virus (ZYMV), the ipomovirus (family Potyviridae ) Cucumber vein yellowing virus (CVYV), the crinivirus (family Closteroviridae ) Cucurbit yellow stunting disorder virus (CYSDV) and the carmovirus (family Tombusviridae ) Melon necrotic spot virus (MNSV) [23-25]. Despite this, not many natural resistance genes have been identified and introgressed into commercial melon cultivars.…”
Section: Introductionmentioning
confidence: 99%